2023
DOI: 10.3390/diagnostics13162640
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence (AI) in a Cephalometric Analysis: A Narrative Review

Abstract: In recent years, the application of artificial intelligence (AI) has become more and more widespread in medicine and dentistry. It may contribute to improved quality of health care as diagnostic methods are getting more accurate and diagnostic errors are rarer in daily medical practice. The aim of this paper was to present data from the literature on the effectiveness of AI in orthodontic diagnostics based on the analysis of lateral cephalometric radiographs. A review of the literature from 2009 to 2023 has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Такі медичні програми з використанням штучного інтелекту стають все більш поширеними [3,4]. У літературі є різні дослідження порівняння різноманітних програм для комп'ютерного цефалометричного аналізу та з використанням звичайного методу.…”
Section: дане дослідження є фрагментом ндр «особливості реабілітації ...unclassified
“…Такі медичні програми з використанням штучного інтелекту стають все більш поширеними [3,4]. У літературі є різні дослідження порівняння різноманітних програм для комп'ютерного цефалометричного аналізу та з використанням звичайного методу.…”
Section: дане дослідження є фрагментом ндр «особливості реабілітації ...unclassified
“…They are essential for improving the interpretation of pictures from many modalities, including PET scans and ultrasounds. Algorithms for automated categorization and feature extraction assist in locating areas of interest and offer crucial data for precise diagnosis [25]. This is especially helpful in the fields of neurology, cardiovascular medicine, and oncology.…”
Section: Medical Imagingmentioning
confidence: 99%
“…A significant number of studies reported a confidence interval within a range of 2 mm, with the mean percentage of accurately identified landmarks being over 80%. Nevertheless, in terms of clinical assessment, a localization error of up to 2 mm may be deemed acceptable for certain sites in a cephalometric examination, but not for all [11]. Precise localization of cephalometric sites A and B in the horizontal plane is essential for determining the maxillary and mandibular relations in the sagittal plane.…”
Section: Introductionmentioning
confidence: 99%